Відображення зсуву інтервалів як об'єднавчий підхід до вивчення динаміки ряду моделей дискретизованих електронних пристроїв - Теплінський, О.Ю. (Видавничий дім "Академперіодика" НАН України, 2008)
The dynamics of quasiperiodically driven interval translation mappings is presented and re-searched. Such mappings, on the one hand, generate simple and general enough discrete-time dynamical systems and, on another, detect common features of a group of mathematical models for widely used discretized electronic devices such as sigma-delta modulators and digital phase-locked loops.